Naming Water Filtration Plants in Jordan: A Thematic Analysis (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
This study is a thematic analysis of the naming practices of water filtration plants in Jordan. The corpus of the data consists of 382 water plants’ names obtained from the Chamber of Commerce in Irbid, Jordan. Each plant’s name in Irbid city is individually analysed and thematically tagged in an excel sheet. The tags for each water plant name are counted. and percentages are extracted. The findings of the study show the following descending order of the major themes: names (48%), religion (17%), quality (16%), wit (4%), patriotism (4%), source (4%), history (3%), technology (3%), drinkware (1%), and romance (1%). The first three themes are the most prominent as they comprise 81% of the data. The three prominent themes have been interpreted in terms of the nature of the Jordanian society. Finally, it is evident that Jordanian filtration water plants’ owners use naming strategies to attract potential customers, mainly via including some familial, tribal, religious and quality symbolism in the names of their plants together with some other minor types of symbolism. Indeed, culture plays a crucial role in different aspects of life in Jordan, including naming practices.
Keywords: Naming; Water Filtration Plants; Jordan; Themes; Motives; Culture